2014
DOI: 10.1530/rep-14-0150
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sympathetic stress impairs follicular development and puberty of the offspring

Abstract: Chronic cold stress applied to adult rats activates ovarian sympathetic innervation and develops polycystic ovary (PCO) phenotype. The PCO syndrome in humans originates during early development and is expressed before or during puberty, which suggests that the condition derived from in utero exposure to neural-or metabolic-derived insults. We studied the effects of maternal sympathetic stress on the ovarian follicular development and on the onset of puberty of female offspring. Timed pregnant rats were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Most studies investigating the effects of prenatal stress on rat reproductive development suggest that, as in this study, effects are more pronounced in the male offspring. However, a recent study by Barra et al (2014) reported that exposure to 4°C for 3h a day throughout pregnancy in rats delayed ovarian follicular development on post-natal days 4 and 30, and delayed the onset of puberty in the female offspring. This study, which used post-pubertal rats, showed no significant alteration in the populations of ovarian follicles, although ovaries from prenatally stressed female rats tended to have more primary follicles.…”
Section: Discussionmentioning
confidence: 96%
“…Most studies investigating the effects of prenatal stress on rat reproductive development suggest that, as in this study, effects are more pronounced in the male offspring. However, a recent study by Barra et al (2014) reported that exposure to 4°C for 3h a day throughout pregnancy in rats delayed ovarian follicular development on post-natal days 4 and 30, and delayed the onset of puberty in the female offspring. This study, which used post-pubertal rats, showed no significant alteration in the populations of ovarian follicles, although ovaries from prenatally stressed female rats tended to have more primary follicles.…”
Section: Discussionmentioning
confidence: 96%
“…The ovaries were dissected under aseptic conditions, placed on sterile lens paper, and cultured on plastic grids at the air/culture medium interface, as previously described (George et al 1987, Barra et al 2014, under an atmosphere consisting of 95% O 2 and 5% CO 2 and at a temperature of 37 8C. One ovary per well was cultured for 8 h in 24-well plates; each well contained 750 ml DMEM/F-12 50:50 v/v (12500, Gibco, Life Technologies).…”
Section: Organ Culturementioning
confidence: 99%
“…In summary, the ovaries from 36 rats were incubated in the presence of every condition, and 36 ovaries (6 per condition) were collected at the end of this period and stored at K80 8C until RNA extraction. The other 36 ovaries were washed in fresh media and incubated for another 24 h with human FSH (F4021, 7000 IU/mg, Sigma Chemical Co.) at a final concentration of 10 IU/ml in incubation media, and the ovaries were fixed to perform morphometric analysis of the follicles, as described previously (Barra et al 2014).…”
Section: Organ Culturementioning
confidence: 99%
“…In addition, some alternative medical treatments, such as acupuncture [132,133], may be mediated by other mechanisms to improve the PCOS disease pattern. Acupuncture can successfully counteract excessive ovarian sympathetic nervous system activity, which is thought to be another possible type of pathophysiology involved in PCOS [134,135]. A recent meta-analysis found that acupuncture can decrease the levels of LH and testosterone and promote the normalization of menstrual cycles in patients with PCOS [136].…”
Section: Discussionmentioning
confidence: 99%